Selbsttötung auf Rezept: eine Begriffsanalyse des Urteils - Bozzaro, Claudia (DMW - Deutsche Medizinische Wochenschrift, 2018)
On March 2, 2017, the Federal Administrative Court in Leipzig ruled: In extreme emergencies, terminally ill people have the right to acquire suicide medications.The purpose of this article is to examine the criteria used to define an “extreme emergency”. The first step is to analyze the verdict. This will show that the term “unbearable suffering” plays a crucial role in defining the “extreme emergency”. In a next step, two philosophical conceptions of the suffering are presented and analyzed with regard to their respective effects for their application in practice. Against this background, it is stated that the application of the criterion of suffering in the judgment is problematic. This leads to the conclusion that the judgment does not constitute a valid basis for practical implementation.
Keywords: Selbsttötung; Gesetz; unerträgliches Leiden; schwere Erkrankung; Lebensende